Politics, polemics and practice: a history of narratives about, and responses to, AIDS in South Africa, 1980-1995 - Tsampiras, Carla (Rhodes University, Faculty of Humanities, Department of History, 2013)
The ongoing urgency of addressing AIDS in South Africa has kept academics and activists focussed primarily on the immediate crises of AIDS 'in the present'. This thesis, covering the period 1980 "“ 1995, examines narratives about, and responses to, AIDS 'in the past' and explores the interplay between these narratives and elites in medical and political communities trying to address AIDS during a period of political transition. The thesis begins by examining the hegemonic medico-scientific narratives about AIDS that featured in the South African Medical Journal, an important site of enquiry as AIDS was primarily conceived of as a 'medical issue'. The SAMJ narratives, which often relied on constructed 'AIDS avatars', framed understandings of the syndrome and influenced responses to it by medical and political communities. The first community that the thesis explores is the African National Congress (ANC) in exile, which had to address AIDS in exile communities and prepare health strategies for 'the new South Africa'. Secondly, the thesis analyses government responses to AIDS and argues that four phases of response can be identified. These phases were characterised by minimum concerns about obtaining information and providing health advice; efforts to gather infection data while exploiting political and public fear; attempts to extend health education and (belatedly) encourage broader engagement; and finally, consultative, democratic ideals. The thesis then examines the National Medical and Dental Association (NAMDA) a progressive medical organisation that worked with the ANC on influential health (and AIDS) strategies. NAMDA members 'crossed over' between various medical and political communities and both reinforced and challenged hegemonic AIDS narratives. Finally, the thesis moves from the abstract, via the practical, to the personal and concludes with a detailed account of the experiences of two sexuality activists at the intersections of these communities and narratives. By focussing on these medical and political communities, and analysing the relationships between these communities, the existing AIDS narratives, and individuals, the thesis also reveals the constructions of morality, 'race', gender, and sexuality that infused them. In doing this it shows how polemic and politics combined to influence practical responses to, and personal experiences of, AIDS.
Keywords: AIDS (Disease) Government policy -- South Africa; AIDS (Disease) Political aspects -- South Africa History; AIDS (Disease) -- South Africa Public opinion History; AIDS (Disease) Social aspects -- South Africa History; South Africa Politics and government 20th century